Germans Suffering in Spain: Cold War Visions of the Spanish Civil War in Fünf Patronenhülsen (1960) and Solange du lebst (1955) - Soldovieri, Stefan (Cinémas, 2007)
AbstractSince 1989 connections between the once geopolitically divided German movie industries have received increasing attention. This article considers how two films of the early post-war period—one produced in East Germany and one from the West—mobilized in different ways figurations of German suffering and sacrifice. The author argues that despite their diverging politics, the two films participate in a trans-German discourse of suffering that persisted in historically variable ways throughout the Cold War period.